THE EXTENT OF BENEFIT DERIVED BY SPECIAL EDUCATION TEACHERS IN NATIONAL CENTERS IN RIYADH CITY FROM FINDINGS OF ACADEMIC RESEARCH AND STUDIES AND THE IMPEDIMENTS OF SUCH BENEFIT - Al-Qahtani, Nourah Abdullah (Journal of Educational and Psychological Sciences, 2019)
This study aimed to recognize the benefit teachers of special education in national centers in the city of Riyadh may derive from findings of academic research and the impediments precluding such benefit in their viewpoints. To this aim, the study has employed the survey descriptive approach. A questionnaire was specifically designed; and applied on 117 members of the sample group, composed of special education teachers, in the city of Riyadh. Findings of the study revealed that the benefit derived by special education teachers from findings of academic research and studies have stood at an average of 2.80 out of 4.00 with verbal grade of ‘Intermediate’. Additionally, findings of the study uncovered a number of impediments that precluded such benefit with an average of 2.42 Out of 3.00 with verbal grade of ‘Intermediate’. At the level of paragraphs, the most significant impediments that precluded benefit of the teachers out of academic research and studies are as follows. Difficulties to employ findings of research and studies, irrelevancy to the issues related to education discipline, lack of motivation among teachers to refer to findings of academic research and studies during the teaching process, inadequate time to have access to such academic research and studies.